The Interplay between Nitrosative Stress, Inflammation, and Antioxidant Defense in Patients with Lichen Planus - Mircea Tampa; Ilinca Nicolae; Corina Daniela Ene; Cristina Iulia Mitran; Madalina Irina Mitran; Clara Matei; Simona Roxana Georgescu (MDPI AG, 2024)
Background: Lichen planus (LP) is a chronic inflammatory skin disease of unelucidated etiology. LP immunopathogenesis is mainly governed by cytotoxic T lymphocytes that mediate an immune response in basal keratinocytes, which may transform into a reservoir of antigens able to initiate an autoimmune reaction. However, other pathogenic pathways complement these mechanisms. Recent studies highlight the involvement of nitrosative stress in the pathogenesis of chronic inflammatory skin diseases. Current data on its role in the pathogenesis of LP are scarce. Methods: In this article, we investigated nitrosative stress in 40 cutaneous LP (CLP) patients compared to 40 healthy subjects using serum markers including nitrosative stress markers-direct nitrite, total nitrite, nitrate and symmetric dimethylarginine (SDMA), total antioxidant status (TAS), and hsCRP, a marker of inflammation, and analyzed the relationship between nitrosative stress, antioxidant defense, and inflammation to offer new insights into the role of the NO pathway in LP pathogenesis. Results: We identified significantly higher serum levels of direct nitrite, total nitrite, nitrate, SDMA and hsCRP, and significantly lower levels of TAS in CLP patients versus controls. There were significant negative correlations between the serum levels of TAS and significantl positive correlations between the serum levels of hsCRP and the analyzed nitrosative stress markers in patients with CLP. Conclusion: Our results indicate an increased level of nitrosative stress in LP patients that correlates with a pro-inflammatory status and altered antioxidant defense.